Pelaksanaan Penyidikan Pelaku Tindak Pidana Penggelapan dalam Jabatan di Unit Satreskrim Polresta Bukittinggi - khozizah, Silvia; Yustrisia, Lola; Zulfiko, Riki (Universitas Ekasakti, 2023)
One type of embezzlement crime is embezzlement in office. The crime of embezzlement in office is regulated in Article 374 of the Criminal Code. Embezzlement in office is a crime committed by a person because of an employment relationship which initially started with a party's trust in another party, which ended with dishonesty of one of the parties, namely the perpetrator of the embezzlement, especially embezzlement often occurs by people who hold goods and is related to their work or position. The purpose of this research is to determine the process of carrying out investigations by the Bukittinggi Police Satreskrim Unit regarding criminal cases of embezzlement in office. The type of research method used in the research is empirical juridical in the form of exploratory research. The results of this research are how the investigation process carried out by Bukittinggi Police investigators was carried out in determining the articles violated by the perpetrators of the crime of embezzlement in office. The obstacle experienced by investigators in carrying out the investigation in this case was the search for the perpetrator and evidence. The investigators' efforts to overcome obstacles in carrying out this investigation were for the Bukittinggi Police Satreskrim Unit investigators to coordinate with the Gunung Tuleh Police in searching for the perpetrator of the crime of embezzlement in office and involving the perpetrator in the search for evidence.